PHILOSOPHICAL EXAMINATION OF DECISION NO. 916/PDT.P/2022/PN SBY: THE PARADIGM OF TRANSCENDENTAL LAW AND MAQÄ€á¹¢ID AL-SYARÄªâ€˜AH - Elviandri; Sutag Harsie; Muhammad Hanafi; Iranda Nadya Febianty; Munir Anshory (Cattleya Darmaya Fortuna, 2025)
This study is a philosophical examination of Surabaya District Court Decision Number 916/Pdt.P/2022/PN Sby through the approach of Transcendental Law and MaqÄá¹£id al-SyarÄ«â€˜ah. The issue of interfaith marriage in the context of Indonesian law reflects the epistemological tension between legal positivism and the divine values that exist in society. The absence of explicit norms regarding the legality of interfaith marriage has encouraged judges to interpret the law formalistically, thereby depriving the law of its ethical and spiritual dimensions. The urgency of this study lies in the pressing need to present a transcendental legal paradigm, namely a law that combines legal rationality with moral values, maqÄá¹£id, and divine justice. This study uses a normative-philosophical legal approach through analysis of court decisions, Islamic legal doctrine, and the principles of modern and prophetic legal philosophy. The methods of analysis include descriptive, hermeneutic, and heuristic approaches to explore the transcendental meaning behind the legal arguments of the decisions. The novelty of this research lies in the formulation of an epistemological synthesis between transcendental law and maqÄá¹£id al-sharÄ«â€˜ah as an alternative paradigm in jurisprudential examination. The findings of this study show that the judges' considerations in this case are still trapped in procedural legalism, without regard to the principles of á¸¥ifáº“ al-dÄ«n (protection of religion) and á¸¥ifáº“ al-nasl (protection of offspring), which are the basic objectives of Islamic law. Transcendental analysis reveals that law is not merely legally valid, but must achieve substantive justice that links legal certainty with moral and spiritual benefits. Thus, this study offers a conceptual model of â€œtranscendental maqÄá¹£id-based lawâ€ as a new direction for national legal reform based on Pancasila.